Environmental conditions steer phenotypic switching in acute hepatopancreatic necrosis disease‐causing Vibrio parahaemolyticus, affecting PirAVP/PirBVP toxins production. (8th January 2020) - Kumar, Vikash; Roy, Suvra; Baruah, Kartik; Van Haver, Delphi; Impens, Francis; Bossier, Peter
Summary: Bacteria in nature are widely exposed to differential fluid shears which are often a trigger for phenotypic switches. The latter mediates transcriptional and translation remodelling of cellular metabolism impacting among others virulence, antimicrobial resistance and stress resistance. In this study, we evaluated the role of fluid shear on phenotypic switch in an acute hepatopancreatic necrosis disease (AHPND)‐causing Vibrio parahaemolyticus M0904 strain under both in vitro and in vivo conditions. The results showed that V. parahaemolyticus M0904 grown at lower shaking speed (110 rpm constant agitation, M0904/110), causing low fluid shear, develop cellular aggregates or floccules. These cells increased levan production (as verified by concanavalin binding) and developed differentially stained colonies on Congo red agar plates and resistance to antibiotics. In addition, the phenotypic switch causes a major shift in the protein secretome. At 120 rpm (M0904/120), PirA VP /PirB VP toxins are mainly produced, while at 110 rpm PirA VP /PirB VP toxins production is stopped and an alkaline phosphatase (ALP) PhoX becomes the dominant protein in the protein secretome. These observations are matched with a very strong reduction in virulence of M0904/110 towards two crustacean larvae, namely, Artemia and Macrobrachium . Taken together, our study provides substantial evidence for the existence of two phenotypic forms in AHPND V. parahaemolyticus strain displaying differential phenotypes. Moreover, as aerators and pumping devices are frequently used in shrimp aquaculture facilities, they can inflict fluid shear to the standing microbial agents. Hence, our study could provide a basis to understand the behaviour of AHPND‐causing V. parahaemolyticus in aquaculture settings and open the possibility to monitor and control AHPND by steering phenotypes.